Development of Test Instrument to Assess Students' Understanding on Macroscopic, Sub-Microscopic, and Symbolic Levels of Acid-Base Topics Using Rasch Model - Sulvianti, Arifah; Aini, Faizah Qurrata (Journal of Educational Sciences, 2023)
Students' conceptual understanding on acid-base topic has not been assessed comprehensively in multiple representation. The test instrument is needed to determine levels of students' understanding on acid-base topic comprehensively. This research developed an instrument to asses students' understanding on acid-base concept based on macroscopic, sub-microscopic and symbolic levels that is claimed valid, reliable, had good difficulty index and discriminatory item. This research is Research and Development (R&D) using Rasch model. The research procedure adopted ten stages by Wei, et al in 2012. The research instrument is questionnaire sheet given to subjects from chemistry lecturers and chemistry teacher. The data were analyzed using Rasch model assisted by minifacet and ministep software. The exact agreement value is 89,2% which have small range from the expect agreement with a percentage of 89,5%. It’s mean that, there is a fit between the results of expert's agreement and the results of estimated model. The pilot test results showed that all items have reached valid criteria based on the MNSQ, ZSTD, and Pt-Mean Corr. The reliability value is 0,80 in the good category. Difficulty index has variations of easy, medium, and difficult items. The discriminatory item is able to distinguish three levels of student ability.